How philosophy can help in creative thinking - Hołub, Grzegorz; Duchliński, Piotr (Creativity Studies, 2016)
In this paper we aim to show that philosophy can be helpful in creative thinking. Although we take into account only selected philosophical concepts and rules, we will try to demonstrate that a person who has a good command over these few ideas can formulate new ideas and projects when confronted with new and demanding situations. Correspondingly, the ability to think abstractly in some specific circumstances can lead to positive and unexpected results. In this way, the mind “plasticity” that results from a philosophical education can become an engine of creativity. This article concerns people who study philosophy (formally or informally) and who in their professional lives are involved in various jobs and activities where creative thinking is needed and even required. In general, the paper is a part of philosophical heuristics.